Penelitian Tindakan Kelas: Antara Teori dan Praktik - Suwartono, Tono (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – For a real educator, instructional activities in the classroom constitute a series of investigations for sustainable quality improvement. However, such classroom inquiries, which are better known as classroom action research in teachers’ world, remain to be seen as exclusive and often neglected, and therefore learning process and outcome become less optimum or even failed. This article aims to examine the gap that exists between the theory and practice of classroom action research and offer its corrections. Methods – This study is based on observation and retrospective interviews during either pre-service or in-service teacher education and training and information obtained from relevant literature. Data/Information regarding the classroom action research practices was confronted with what experts in the field “say”. Findings – Some important points on teachers’ bad practices in implementing classroom action research, and most possible causes, as well as their proper practices, have been crystallized through this review. Research Implications – At the end of this paper, teachers are offered some ways that prevent them from misconceiving and wrongly implementing classroom action research.